Cattle research network newsletter - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
quarterly publication, the'Cattle Research Network Newsletter ILCA - PO Box 5689 - Addis Ababa - ETHIOPIA